2017
DOI: 10.1016/j.diabres.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Weight change after initiation of oral hypoglycemic monotherapy for diabetes predicts 5-year mortality: An observational study

Abstract: Purpose To investigate whether weight change in the first year after initiating an oral hypoglycemic agent (OHA) for type 2 diabetes treatment is associated with mortality in a national cohort. Procedures We prospectively followed Veterans Health Administration patients with type 2 diabetes initiating treatment with an OHA and not receiving any other diabetes pharmacotherapy for at least one year. Information on OHAs, weight, co-morbidities, other medications, demographics, and laboratory measurements was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…An analysis from the Veterans Health Administration (VHA) including 145 198 patients treated with oral antidiabetic therapy showed that weight loss of >5% body weight but not weight gain was consistently associated with higher risk of 5-year mortality. 27 We have previously reported on weight change in patients with DM and CV comorbidity of the PROactive study. 28 In this patient cohort, weight loss was associated with higher mortality compared to patients with no weight loss while weight gain had no negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis from the Veterans Health Administration (VHA) including 145 198 patients treated with oral antidiabetic therapy showed that weight loss of >5% body weight but not weight gain was consistently associated with higher risk of 5-year mortality. 27 We have previously reported on weight change in patients with DM and CV comorbidity of the PROactive study. 28 In this patient cohort, weight loss was associated with higher mortality compared to patients with no weight loss while weight gain had no negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that weight gain ≥ 10% was related to an unhealthy lifestyle (current smoking/heavy alcohol drinking), as indicated in Table 1 . It was previously reported that weight gain while taking metformin may be a marker for poor compliance with antidiabetic medication, which has been reported to be associated with higher mortality [ 20 ]. Weight gain may occur because of treatment with insulin or other hypoglycemic agents such as sulfonylurea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study did not assess the muscle mass, which may be an important factor for prognosis. Third, while it is known that each category of diabetic drug may affect body weight (32), information about diabetic medications before admission was not collected. Lastly, this study may be subjected to the selection bias because a significant portion of screened patients excluded according to the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%